2004
DOI: 10.1161/01.str.0000124459.33597.00
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption and Risk of Stroke Among Middle-Aged Men: The JPHC Study Cohort I

Abstract: MD; for the JPHC Study GroupBackground and Purpose-The impact of light-to-moderate alcohol consumption on risk of stroke has not been well examined in a single study, although the effect is hypothesized to differ among stroke subtypes from meta-analyses. Methods-A total of 19 544 men aged 40 to 59 years living in communities were followed-up from 1990 to 1992 to the end of 2001 in the Japan Public Health Center-based Prospective Study on Cancer and Cardiovascular Disease (JPHC Study). Results-After 214 504 per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
105
3
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 173 publications
(121 citation statements)
references
References 27 publications
11
105
3
2
Order By: Relevance
“…A positive linear relationship has been observed between the level of alcohol consumption and risk of brain or subarachnoid hemorrhage. 8,110,116,117 Actions on the BP and blood coagulation system seem to be underlying mechanisms for this adverse influence of alcohol.…”
Section: Cerebrovascular Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…A positive linear relationship has been observed between the level of alcohol consumption and risk of brain or subarachnoid hemorrhage. 8,110,116,117 Actions on the BP and blood coagulation system seem to be underlying mechanisms for this adverse influence of alcohol.…”
Section: Cerebrovascular Diseasementioning
confidence: 99%
“…110,[116][117][118] The low risk in light drinkers seems to be due to the lower degree of atherosclerosis and the inhibition of blood coagulation, as in the case of ischemic heart disease. The increased risk in heavy drinkers is probably related to increases in the level and variability of the BP, hemoconcentration because of dehydration and thromboembolism associated with alcohol-induced atrial fibrillation.…”
Section: Cerebrovascular Diseasementioning
confidence: 99%
“…An 11-year follow-up of the JPHC Study of 19,544 men aged 40 to 59 years 27) showed that alcohol consumption was associated with an elevated risk of total stroke for drinkers with an alcohol intake of 450 g ethanol per week compared with occasional drinkers. This excess risk was confined primarily to hemorrhagic stroke with a multivariable HR of 2.15 (95% CI: 1.22-3.79).…”
Section: Alcohol Consumptionmentioning
confidence: 99%
“…[6][7][8][9] The U-shaped relationship between alcohol intake and ischemic stroke and the alcohol-dependent increase in hemorrhagic stroke were also observed in Japan. 10) Favorable associations between light-to-moderate alcohol intake and health issues have been suggested, but most of the studies were conducted without attention to the type of alcoholic beverages consumed. Several epidemiological studies have described the association of the type of alcoholic beverage with health problems, but no differences were observed in the type of alcoholic beverage consumed.…”
Section: Hepatoprotective Effects Of a Concentrate And Components Of mentioning
confidence: 99%